2018
DOI: 10.1093/rheumatology/key041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and molecular aspects of phosphoribosylpyrophosphate synthetase superactivity in females

Abstract: Objectives. Phosphoribosylpyrophosphate synthetase (PRPS1) superactivity is an X-linked disorder characterized by urate overproduction Online Mendelian Inheritance in Man (OMIM) gene reference 300661. This condition is thought to rarely affect women, and when it does, the clinical presentation is mild. We describe a 16-year-old African American female who developed progressive tophi, nephrolithiasis and acute kidney failure due to urate overproduction. Family history included a mother with tophaceous gout who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Gout usually occurs between the fourth and sixth decade of life. Pediatric-onset of hyperuricemia and gout in clinical practice is rare and suggestive of a genetic disorder as PRPS1 superactivity [ 5 ] and hypoxanthine-guanine phosphoribosyltransferase deficiency [ 6 ], especially when a strong family history is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Gout usually occurs between the fourth and sixth decade of life. Pediatric-onset of hyperuricemia and gout in clinical practice is rare and suggestive of a genetic disorder as PRPS1 superactivity [ 5 ] and hypoxanthine-guanine phosphoribosyltransferase deficiency [ 6 ], especially when a strong family history is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the down‐regulation of PRPS1 might disturb kidney recovery. Furthermore, a previous study reported that PRPS1 superactivity was a rare X‐linked disorder, and that when PRPS1 activity was increased, it resulted in an increase in purine production . Therefore, it was speculated that the purine production was decreased in the present study.…”
Section: Resultsmentioning
confidence: 67%
“…Patients with severe or extremely high PRPS1 superactivity may exhibit one or more of the following nine missense PRPS1 mutations, p.D52H (c.154G > C), p.L129I (c.385C > A), p.A190V (c.569C > T), p.H193Q (c.579C > G) [ 151 ], p.N114S (c.341A > G) and p.D183H (c.547G > C) [ 118 , 151 ], p.H193L (c.578A > T) [ 150 , 151 ], p.G174V (c.521G > T) [ 162 ] and p. G174R (c.520G > A) [ 163 ]. Specifically, the missense mutations of p.D52H and p.L129I result in the disruption of local structure close to the allosteric sites and therefore inhibit feedback regulation [ 118 , 151 , 164 ].…”
Section: Human Prps and Associated Disordersmentioning
confidence: 99%
“…In males, PRPS1 superactivity resulted in an alteration in the allosteric control of PRPP synthesis with high purine nucleotide and uric acid production [ 17 ]. However, the study of Zikánová et al (2018) [ 163 ] showed that female carriers of PRPS1 superactivity had elevated levels of uric acid and gout since random X-chromosome inactivation may result in them retaining only the mutated allele p.G174R (c.520G > C).…”
Section: Human Prps and Associated Disordersmentioning
confidence: 99%